The Effect of Lactation Massage on Breast Milk Production in Postpartum Mothers - Viky Aulia Restyo; Rifzul Maulina (KHD Production, 2026)
Inadequate breast milk production remains a common challenge among postpartum mothers, often associated with hormonal imbalance, maternal fatigue, and insufficient breast stimulation, which can hinder the achievement of exclusive breastfeeding targets. Despite global recommendations, exclusive breastfeeding rates remain suboptimal, highlighting the need for effective, non-pharmacological interventions. Lactation massage has been proposed as a technique to stimulate oxytocin release and improve the milk ejection reflex. This study aimed to evaluate the effect of lactation massage on breast milk production among postpartum mothers. A quasi-experimental study with a pretest–posttest control group design was conducted involving 20 postpartum mothers selected through purposive sampling. Participants were equally assigned to intervention and control groups. The intervention group received lactation massage for three consecutive days, while the control group received standard postpartum care. Breast milk production was measured by expressed milk volume using a breast pump for 10–15 minutes at 08:00 a.m. daily. Data were analyzed using appropriate statistical tests with a significance level set at p < 0.05. The intervention group demonstrated a significant increase in mean breast milk production, from 45.2 mL at baseline to 77.6 mL post-intervention, with a mean difference of 32.4 mL (p < 0.001). In contrast, the control group showed no statistically significant change (p = 0.214). Between-group analysis revealed a significant difference in posttest milk production (p < 0.001). Lactation massage significantly enhances breast milk production in postpartum mothers. This simple, non-invasive intervention may be integrated into routine postpartum care to support optimal breastfeeding outcomes.